Changes of gene expression but not cytosine methylation are associated with male parental care reflecting behavioural state, social context, and individual flexibility - Chris Cunningham (The Journal of Experimental Biology, 2018)
Behaviour is often on the front line response to changing environments. Recent studies show behavioural changes are associated with changes of gene expression; however, these studies have primarily focused on discrete behavioural states. We build on these studies by addressing additional contexts that produce qualitatively similar behavioural changes. We measured levels of gene expression and cytosine methylation, which is hypothesized to regulate the transcriptional architecture of behavioural transitions, within the brain during male parental care of the burying beetle Nicrophorus vespilloides in a factorial design. Male parenting is a suitably plastic behaviour because while male N. vespilloides typically do not provide direct care (i.e., feed offspring) when females are present, levels of feeding by a male equivalent to the female can be induced by removing the female. We examined three different factors: behavioural state (caring vs non-caring), different social contexts (with or without a female mate), and individual flexibility (if a male switched to direct care after his mate was removed). The greatest number of differentially expressed genes were associated with behavioural state, followed by social contexts, and lastly by individual flexibility. Cytosine methylation was not associated with changes of gene expression in any of the conditions. Our results suggest a hierarchical association between gene expression and the different factors, but that this process is not controlled by cytosine methylation. Our results further suggest that the extent a behaviour is transient plays an underappreciated role in determining its underpinning molecular mechanisms.